James - Giese, Curtis P (Saint Louis : Concordia Publishing House, 2021)
"This commentary on the epistle of James provides an original translation, meticulous grammatical analysis of the Greek text, and theological exposition addressing perpetual issues in the life of the church and highlighting the enduring relevance of this epistle for Christians amid trials. The author presents careful research into the historical context, purpose, structure, and message of James, which has often been misunderstood, notably in the Lutheran tradition. Dr. Giese offers a positive, corrective interpretation. The overarching theme of James is "the gifts of the giving God and their use." James 1:16-18 stands as the theological center of the book: the eschatological gift of rebirth in Jesus Christ, to be firstfruits of the new creation, establishes the right use of all other divine gifts"--
The authorship of James -- The date of James -- The addressees of James and their situation -- Old Testament and New Testament connections in James -- The structure of James -- The eschatological focus of James -- Law and gospel in James -- The reception of James in the early church -- Luther and James -- 1:1-27. James' "table of contents" for his entire epistle -- 2:1-26. James' integral connection of faith and deeds -- 3:1-18. James' focus on the tongue and wisdom -- 4:1-17. James' focus on one's will and slander -- 5:1-20. James' focus on wealth and the Parousia.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries